Peranan Pemerintah dalam Pengelolaan Pariwisata Menurut Undang-undang Nomor 10 Tahun 2009 - Sukarno, Sukarno (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2016)
Tourism in the era of regional autonomy is the realization of the ideals of the nation of Indonesia to promote common kesejahteraan and participate in implementing world order based on freedom, lasting peace and social justice.